The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1152/ajpendo.00282.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism is associated with decreased expression of processed myostatin in males

Abstract: Myostatin inhibits skeletal muscle development. Therefore, we sought to determine whether larger body and muscle mass in male mice was associated with lower mRNA and protein expression of myostatin compared with females. Ten male and ten female mice of the C57 strain were killed at 16-18 wk of age, and their biceps femoris, gastrocnemius, and quadriceps femoris muscles were collected. Body and muscle masses were 40% heavier (P < 0.001) in males than in females. Northern analysis showed no difference in mRNA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
39
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 26 publications
10
39
2
3
Order By: Relevance
“…This hypothesis fits well, too, with the dearth of mitochondria, which can act as fast calcium sinks in skeletal muscle (31) as well as providing ATP for calcium uptake into the sarcoplasmic reticulum; their lack in Mstn Ϫ/Ϫ might well stimulate a compensatory formation of the sarcoplasmic reticulum. Intriguingly, small numbers of tubular aggregates are found in muscles of older male wild-type mice of the reference wild type used here and of various inbred and outbred laboratory mouse strains (32,33) but not in wild-type females, which correlates with the higher level of myostatin in wild-type female than male muscle (34).…”
Section: Discussionmentioning
confidence: 71%
“…This hypothesis fits well, too, with the dearth of mitochondria, which can act as fast calcium sinks in skeletal muscle (31) as well as providing ATP for calcium uptake into the sarcoplasmic reticulum; their lack in Mstn Ϫ/Ϫ might well stimulate a compensatory formation of the sarcoplasmic reticulum. Intriguingly, small numbers of tubular aggregates are found in muscles of older male wild-type mice of the reference wild type used here and of various inbred and outbred laboratory mouse strains (32,33) but not in wild-type females, which correlates with the higher level of myostatin in wild-type female than male muscle (34).…”
Section: Discussionmentioning
confidence: 71%
“…The sexually dimorphic difference in GDF-11 expression coincides with the divergent growth between sexes which occurs from about six weeks of age in mice [15]. In comparison, we have shown that there are higher concentrations of mRNA and decreased mature myostatin protein in male than in female muscles and have shown that these differences are developmentally regulated by growth hormone [15,19]. The concentration of GDF-11 mRNA is higher in males than females which would seem to be inconsistent with the greater muscle mass in males than females if we assume that GDF-11 is an inhibitor of muscle development.…”
Section: Discussionmentioning
confidence: 61%
“…Although the precise mechanisms that account for these gender differences in myostatin effects are unknown, these data suggest that there may be gender-specific mechanisms that can override the effects of myostatin on muscle mass in female transgenic mice. This interpretation is supported by the recent demonstration that decreased abundance of processed myostatin in young wild-type mice is associated with increased body mass and skeletal muscle mass in male compared with female animals (22). It is possible that association with other proteins, more abundant in females than in males, may partially inactivate myostatin in females despite the higher levels seen in this sex, as has been shown to occur in transgenic mice overexpressing follistatin (17).…”
Section: Discussionmentioning
confidence: 72%